THE FORMATION OF THE CONTRACT IN THE UN CONVENTION ON THE INTERNATIONAL SALE OF GOODS: A COMPARATIVE ANALYSIS - Giulio Giannini (Nordic Journal of Commercial Law, 2006)
A contract is formed when parties express their agreement in congruent declarations, a prior offer and a consequence acceptance. For a long time there was no practical need to force consent into the structure of offer and acceptance because parties always made their contracts face to face. In Rome, for example, contractual obligations were originally made by stipulatio, for which the parties needed to be physically present together, and even when this formality was dropped, contracts generally continued to be made in the presence of the parties, possibly represented by a slave or a soninpower or even a free man appointed for that purpose. As a consequence the Roman jurists never came to think of two declarations named “ offer” and “ acceptance” as necessary for consent.1 The need for the agreement of the parties expressed in the offer and acceptance arose when a reliable postal service and contracting at a distance became possible; but even if no difficulties arise when the contract is concluded between parties who are in the same place or in immediate communication, when a contract is to be concluded inter absentes, and, after their declarations, it takes time for each of them to reach its addressee, several questions can arise. In many cases in which a contract has unquestionably been formed, it is impossible, unrealistic or arbitrary to regard the conduct of one party as an offer and that of the other as an acceptance2; the stipulatio in a sale of land or the case of a customer who pays cash for a packet of cigarettes are situations in which it is difficult to say that one party is making an offer to the other who is declaring his acceptance. Another important situation is where an agreement is reached only after a long period of negotiation such as in a typical export sale where none of the letters exchanged may be defined as an offer or an acceptance. Nevertheless there are other forms of reaching agreement (e.g., agreement reached in a pointbypoint negotiations or with a performance) where the ‘dissection’ of individual statements as ‘offer’ and ‘acceptance’ would constitute an arbitrary legal operation as in the criticized decision of a US federal court in Filanto S.p.A. v. Chilewich International Corp.3 in which the memorandum was considered as an offer and the seller’s conduct as an acceptance in a possible but certainly not mandatory way.4 This paper deals with this important requirement for the effective conclusion of a sale contract achieved by means of offer and acceptance. The starting point will be the Part Two of the UN Convention on the International Sales of Goods (CISG)5 but each aspect of the latter objective agreement will be discussed in a comparative analysis with the three most important legal systems, namely the AngloSaxon legal family where the offeror is the least bound, the German system in which he is most strongly bound and the Romanistic one which adopts an intermediate position.